Bootstrap Uniform Confidence Bands for A Local Linear Nonparametric Estimator and Applications to Financial Risk Management - Ananda, O. K.; Mwita, Peter N. (My University, 2012)
This paper considers the problem of bootstrapping a local linear estimator in conditional quantile estimation of a financial time series assuming independent and identically distributed errors. A nonparametric regression bootstrap generating process is estimated, then bootstrap confidence bands fitted to the quantile estimates. Under appropriate assumptions, the local linear bootstrap estimator is known to be consistent
Keywords: Quantile estimation; Bootstrap; Local linear; Consistency